Are we Cyber aware? A cross sectional study on the prevailing Cyber practices among adults from Thiruvalla, Kerala. - Sebastian, Shaliet Rose; Babu, Bichu P. (International Journal Of Community Medicine And Public Health, 2022)
Background: Cyber-crime is described as any unlawful activity which is committed using any computing devices, like computer/smartphone and which is a part of internet. There are different methods by which cyber-crime is committed which include 1) attacks on computer systems, 2) cyber-bullying, 3) email spam, 4) phishing, 5) identity theft. Breaches in cyber security have become a severe danger to world security and the economy, compromising essential infrastructure and wreaking havoc on company performance, resulting in significant cognitive property loss. It is a sad reality that cybercrime cases have witnessed a steady spike. India has witnessed a significant increase in cases of cyber fraud and various cyber-related incidents in the last three years. The present study was done to assess the prevailing cyber practices among adults from Thiruvalla, Kerala. Methods: The present cross-sectional study was conducted among 340 adults in Thiruvalla, Kerala from January to June, and 2022. A semi-structured questionnaire was used to elicit information from the study participants after obtaining consent. The quantitative data collected was analysed using the software statistical package for social sciences. The results have been presented as tables and charts showing frequencies and percentages. Results: 133 out of the 350 study participants (38%) believed that it was important to be aware of cyber security risks in general while 52% (182) of the study participants considered cyber security awareness to be the only solution to the existing online scams. Conclusions: Widespread awareness campaigns are necessary to improve the cyber awareness of the community and thereby improve their cyber practices.